Back to the Face-to-Face classroom: instructors' perceptions on students' performance - Dreifuss-Serrano, Cristina (2022)
After almost two years of exclusive online formats for higher education, students recently returned to campus and face-to-face activities. Even though this was much awaited, the perceived results from the instructors' point of view seem to show that students are not as prepared as they were in face-to-face environments before the pandemic. Using a survey, we obtain information on the perceptions of studio instructors, in several universities in Lima, Peru. Asking questions about students' performances in the specific parts of the process, and about the instructors' perceptions of their own attitudes and methods, we established which specific aspects seemed to have been most affected by the changes in education format. Most instructors agree that students' performance has worsened after going back to face-to-face classrooms, when compared to their teaching before the pandemic. We take this opportunity to reflect on the transitions from physical to virtual and back to physical environments, and the opportunities they present for reflection and evaluation on our teaching approaches.